Modification method and application of high-entropy oxide catalyst

The high entropy oxide catalyst is modified through the combined treatment method of superhydrophobic surface treated by soft film plate and ball mill, which solves the problem of limited removal of VOCs and large interference in complex flue gas, and achieves high water vapor Highly efficient catalytic oxidation in the environment.

CN119425718APending Publication Date: 2025-02-14HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411329988.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing high-entropy oxide catalysts have limited effect on volatile organic matter (VOCs) in complex flue gases and are greatly disturbed by water vapor, which affects their catalytic oxidation behavior.

Method used

Using the superhydrophobic surface combined treatment method of soft film plate and ball mill, the high entropy oxide catalyst is modified through two steps of ball milling and acid etching, and its specific surface area and surface roughness are increased, thereby forming a superhydrophobic air intercept layer and reducing Water vapor interference.

Benefits of technology

The high-entropy oxide catalysts have significantly improved the removal ability of VOCs in complex flue gases, and can maintain catalytic efficiency in a high water vapor environment, and can resist up to 30vol.% water vapor interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425718A_ABST
    Figure CN119425718A_ABST
Patent Text Reader

Abstract

The invention relates to a high-entropy oxide catalyst with improved performance of catalyzing VOCs (volatile organic compounds) in wet flue gas and a preparation method of the high-entropy oxide catalyst. The preparation method comprises the following steps: crushing a large high-entropy oxide catalyst into small substances by using a soft diaphragm plate to assist ball milling, so that the reaction site and the compensation site of the catalyst are exposed more obviously, and the specific surface area of the catalyst is increased; therefore, more sufficient mutual infiltration with acid liquor can be realized, and favorable preconditions are provided for the next step of acid etching treatment; then, acid etching treatment is further utilized, after the high-entropy oxide is subjected to acid etching treatment, due to different dissolvability of metal atoms in the high-entropy oxide, the dissolution speed and the dissolution sequence are different, and then differential dissolution occurs; the surface roughness of the high-entropy oxide is further improved, so that a super-hydrophobic air interception layer is formed on the surface of the high-entropy oxide; according to the method, the water resistance of the high-entropy oxide in the complex flue gas is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular to a high entropy oxide catalyst and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) are defined in my country's latest standard "Volatile Organic Compounds Unorganized Emission Control Standard" (GB37822-2019) as: organic compounds that can participate in atmospheric photochemical reactions, or organic compounds determined in accordance with relevant regulations. Since VOCs can participate in atmospheric photochemical reactions, their emissions will accelerate the formation of secondary pollutants such as fine particulate matter (PM2.5) and ozone (O3), and are the culprit for environmental problems such as acid rain, photochemical smog, ozone depletion and greenhouse effect. Similarly, most VOCs have an unpleasant irritating odor and are toxic, teratogenic and carcinogenic to the human body. In particular, aromatic compounds containing benzene and biphenyls such as benzene, toluene and naphthalene can cause greater harm to human health.

[0003] Among the existing technical means, it is feasible to use catalytic oxidation to treat pollutants in coal-fired flue gas, but the existing research mainly focuses on the exploration of the catalytic activity of catalysts. There is still a lack of research on the interference of other toxic gases in complex flue gas, among which the interference of water vapor on the catalytic oxidation of catalysts is particularly serious. In modern process equipment, the catalytic oxidation equipment of VOCs is generally set after the flue gas desulfurization. After passing through a long flue gas pipeline, the flue gas temperature is relatively low and the water vapor content is relatively high. For example, in the coal-fired flue gas of a thermal power plant, the water vapor content ranges from 3vol.% to 10vol.%, and can reach up to 15vol.%. Water vapor will affect the catalytic oxidation behavior of the catalyst for VOCs through competitive adsorption, surface hydroxyl generation, changing the reaction path of the catalyst, and changing the final product. Therefore, water vapor has a huge impact on the catalytic oxidation of VOCs.

[0004] High entropy catalysts, which are single-phase solid solutions formed by random mixing of five or more transition metal elements in nearly equimolar amounts, are considered to have good catalytic performance due to their unique high entropy configuration, rich types of constituent metals, and lattice distortion. Their entropy-stabilized structure can effectively promote the mutual dissolution of metals and inhibit phase separation, and can remain stable even under harsh conditions; due to the rich types of constituent metals, the lattice distortion induced by the single-phase solid solution formed by co-doping of different metals will also bring more active sites and oxygen vacancies, which are all favorable conditions for catalytic reactions. At present, high entropy oxides have been widely used in the field of catalysis. However, in practical applications, high entropy catalysts are still plagued by the problem of insufficient water resistance. The above problems are related to the large particle size and low dispersion of high entropy oxides themselves, which is related to their preparation principle: the formation of high entropy oxides originates from the minimization of the Gibbs free energy (ΔG) of the system. In order to maintain this specific configuration, high temperature conditions are generally required in the preparation process. However, too high a temperature is bound to cause meaningless growth of the lattice, which in turn affects the dispersion of the sample, resulting in reduced catalytic efficiency and water resistance of the sample.

[0005] In response to the above problems, a large number of methods for preparing nano high entropy oxides have been developed. These methods are bottom-up synthesis methods that use atoms and molecules as building blocks, assemble them with molecular or atomic precision, and precisely control the size and shape. This method is expensive and has extremely small output, and is not suitable for rapid and large-scale industrial production.

[0006] Therefore, there is an urgent need for a new type of super-hydrophobic surface combined treatment method that can directly improve the super-hydrophobicity of samples prepared by existing processes, and its actual effect is also very excellent. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high entropy oxide catalyst and its preparation method and application, which can enhance the removal effect of the high entropy oxide catalyst on VOCs in complex flue gas and effectively reduce the influence of water vapor on the high entropy oxide catalyst.

[0008] The present invention solves the technical problem by adopting the following technical solutions:

[0009] A method for modifying a high entropy oxide catalyst comprises the following steps:

[0010] S1. preparing a surfactant;

[0011] S2, adding grinding balls and a high entropy oxide catalyst into a ball mill, and adding the surfactant obtained in step S1, and performing a ball milling reaction. After the ball milling reaction is completed, ethanol is added for washing until the supernatant is clear, not light yellow, and the pH is not acidic, thereby obtaining a ball milled catalyst;

[0012] S3, adding the ball-milled catalyst to deionized water to form a suspension, and adding a final concentration of H + The acidic solution with a concentration of 0.01 to 0.1 M is stirred, the obtained precipitate is filtered, washed with deionized water, and dried to obtain a modified high entropy oxide catalyst.

[0013] Moreover, the surfactant is a surfactant formed by mixing oleic acid and oleylamine in a mass ratio of 1:1.

[0014] Moreover, the solvent for dissolving the oleic acid and oleylamine is n-heptane or carbon tetrachloride.

[0015] Moreover, the mass of the surfactant is 10% to 50% of the mass of the high entropy oxide catalyst.

[0016] Moreover, the amount of the surfactant is 15 wt %.

[0017] Moreover, the acidic solution is a nitric acid solution, a sulfuric acid solution or a hydrochloric acid solution, and the concentration of the acidic solution is 0.06M; the ball-to-material ratio of the ball mill is 5-20:1, the ball milling rate is 1200-1500r / min, and the ball milling time is 12-36h.

[0018] Moreover, the high entropy oxide catalyst is a spinel high entropy oxide, a fluorite high entropy oxide,

[0019] (CrMnFeCoCe)3O4, (MnLaCePrSm)O2 or (CoMnCuAlFe)3O4.

[0020] A high entropy oxide catalyst is modified by the above-mentioned high entropy oxide catalyst modification method.

[0021] An application of the high entropy oxide catalyst in catalytic removal of VOCs in wet flue gas.

[0022] Moreover, wet flue gas contains 30% water vapor.

[0023] The advantages and positive effects of the present invention are:

[0024] 1. The present invention proposes a technical method of combined treatment of soft film plate and ball milling to alleviate the influence of water vapor on high entropy catalyst. First, the large pieces of high entropy catalyst are broken into small pieces by ball milling assisted by soft film plate, so that the catalyst reaction sites and compensation sites are more obviously exposed, and its specific surface area is increased, so that it can be more fully infiltrated with acid solution, providing a favorable prerequisite for the next step of acid etching treatment. Subsequently, the high entropy oxide will be further treated with acid after acid etching, due to the different solubility of the metal atoms therein, resulting in different dissolution rates and dissolution orders, and then differential dissolution will occur. This will further increase its surface roughness. A super-hydrophobic air retention layer is formed on the surface of the high entropy oxide, which effectively reduces the influence of water vapor on the high entropy oxide catalyst.

[0025] 2. The present invention adopts a new type of super-hydrophobic surface joint treatment method. This method does not require the development of a new preparation process for nano-scale high-entropy catalysts, and can directly improve the super-hydrophobicity of samples prepared by existing processes; and its actual effect is also very excellent. In the current experiment, the high-entropy oxide can resist the interference of up to 30% water vapor, and complete the catalytic oxidation of pollutants such as o-xylene in this environment. This modification technology can be directly applied in industry and has strong economic value.

[0026] 3. The present invention uses the opposite top-down soft film plate ball milling and acid etching combined treatment to modify the high entropy oxide prepared by high temperature. This is a method that uses the mechanical force of the ball milling process and the acid solubility difference of metal atoms to decompose large blocks of high entropy oxide materials into small particle systems to increase specific surface area, dispersion and surface roughness. After modification by this means, the hydrophobicity of the high entropy oxide sample is greatly increased. It can effectively resist the interference of up to 30vol.% water vapor.

[0027] 4. Compared with the existing bottom-up methods such as surface chelation method and salt-assisted filling method, the present invention has lower actual cost and can be directly used in large-scale industrial production. There is no need to make too many modifications to the existing high entropy oxide preparation technology. It only needs to perform simple subsequent modification treatment on the prepared high entropy oxide. Moreover, the dispersion and water resistance of the modified high entropy oxide are much higher than those of other existing treatment methods, which can effectively improve its water resistance in complex flue gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a test diagram of the hydrophobic angle of the (CrMnFeCoCe)3O4 surface after ball milling and acid etching combined modification in Example 1 of the present invention.

[0029] Figure 2This is a graph showing the water resistance of (CrMnFeCoCe)3O4 at 150°C to 250°C after ball milling and acid etching combined modification in Example 1 of the present invention.

[0030] Figure 3 This is a test diagram of the hydrophobic angle of the (MnLaCePrSm)O2 surface after ball milling and acid etching combined modification in Example 2 of the present invention.

[0031] Figure 4 This is a graph showing the water resistance of (MnLaCePrSm)O2 at 60°C to 100°C after ball milling and acid etching in Example 2 of the present invention.

[0032] Figure 5 This is a diagram of the toluene catalytic efficiency of (CrMnFeCoCe)3O4 at 0°C to 400°C after ball milling and acid etching combined modification in Examples 3-7 of the present invention.

[0033] Figure 6 This is a test diagram of the hydrophobic angle of the (CrMnFeCoCe)3O4 surface without modification in Comparative Example 1 of the present invention.

[0034] Figure 7 This is a graph showing the water resistance of (CrMnFeCoCe)3O4 at 150°C to 250°C without modification in Comparative Example 1 of the present invention.

[0035] Figure 8 This is a test diagram of the hydrophobic angle of the surface of (CrMnFeCoCe)3O4 that was only subjected to ball milling modification in Comparative Example 2 of the present invention.

[0036] Fig. 9 This is a graph showing the water resistance of (CrMnFeCoCe)3O4 at 150°C to 250°C after only ball milling modification in Comparative Example 2 of the present invention.

[0037] Fig.10 This is a test diagram of the hydrophobic angle of the (CrMnFeCoCe)3O4 surface that was only treated with acid etching in Comparative Example 3 of the present invention.

[0038] Fig.11 This is a graph showing the water resistance of (CrMnFeCoCe)3O4 at 150°C to 250°C after only acid etching modification in Comparative Example 3 of the present invention.

[0039] Fig.12 Schematic diagram of the equipment used to test water resistance during the catalytic process.

[0040] Reference numerals:

[0041] a. Mass flow meter; b. Volume flow meter; c. Place in constant temperature water tank; d. Gas washing bottle; e. Gas mixing bottle; f. Constant temperature tube furnace; g. Quartz reactor; h. Catalyst; i. VOCs tester; j. Temperature controller; k. Flue gas analyzer. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0043] A method for modifying a high entropy oxide catalyst comprises the following steps:

[0044] S1. preparing a surfactant;

[0045] S2, adding grinding balls and a high entropy oxide catalyst into a ball mill, and adding the surfactant obtained in step S1, and performing a ball milling reaction. After the ball milling reaction is completed, ethanol is added for washing until the supernatant is clear, not light yellow, and the pH is not acidic, thereby obtaining a ball milled catalyst;

[0046] S3, adding the ball-milled catalyst to deionized water to form a suspension, and adding a final concentration of H + The acidic solution with a concentration of 0.01 to 0.1 M is stirred, the obtained precipitate is filtered, washed with deionized water, and dried to obtain a modified high entropy oxide catalyst.

[0047] The surfactant used in the ball milling of the present invention is a mixture of oleic acid (purity 99%) and oleylamine (purity 98%) in equal proportions, which are pre-dissolved in n-heptane (purity 99.8%). The n-heptane is used only as a solvent, and the amount used should be as small as possible. The mixture of oleic acid and oleylamine in equal proportions is the main component of the surfactant. The amount of the surfactant is only calculated as the mass of oleic acid and oleylamine and is 10% to 50% of the mass fraction of the ball milled sample powder (the mass ratio of oleylamine to oleic acid is 1:1).

[0048] Oleic acid is a long-chain fatty acid with a carbon-carbon double bond and a carboxyl group in its molecule. n-heptane is a non-polar solvent. According to the principle of "like dissolves like", the long carbon chain part of oleic acid has a certain non-polarity, which is similar to the non-polarity of n-heptane, making oleic acid have a good solubility in n-heptane.

[0049] Oleylamine is an unsaturated fatty amine with a long carbon chain and an amino group in its molecule. The non-polar environment of n-heptane can interact with the long carbon chain of oleylamine, making it well soluble in n-heptane.

[0050] Similarly, by removing the polar part of the long carbon chain of oleic acid and oleylamine, the carboxyl and amino groups in the non-polar segment can also couple with each other, and the three can be more closely combined into a whole, thereby reducing the surface tension of n-heptane and forming a stable interfacial active layer, so that n-heptane can more easily infiltrate the ball-milled sample and enhance the dispersibility of the ball-milled sample.

[0051] During the ball milling process, a ball-to-material ratio of 10:1 is used, and a high entropy oxide catalyst and grinding balls are added to each ball mill, and a prepared surfactant is added. The ball milling time is 18h and the surfactant dosage is 15wt.% as the optimal selection. After the ball milling is completed, a large amount of ethanol is added to the ball mill to rinse, and the washed black suspension is transferred to a beaker. Let it stand for 30 minutes until the solution is separated, and the supernatant is poured out. Repeat this process 5 to 7 times until the poured supernatant is clear, not light yellow, and the pH value is not acidic. At this point, the ball milling is completed.

[0052] The acid solution used for acid etching is nitric acid solution. + Concentrated nitric acid solution was mixed with deionized water to make H + The concentration was adjusted to 0.01-0.1M.

[0053] 1 g of the ball-milled sample was added into 50 mL of deionized water solution and stirred thoroughly. Then, nitric acid solution was added into the obtained suspension and stirred at room temperature for 1 h. The obtained precipitate was filtered, washed with deionized water, and dried at 80 °C for 12 h. Thus, the surface acid etching ball milling modification was completed.

[0054] Example 1

[0055] A method for modifying a high entropy oxide catalyst, in this embodiment, a 0.06M concentration nitric acid solution is used to acid-etch and ball-mill the high entropy oxide catalyst (CrMnFeCoCe)3O4, comprising the following steps:

[0056] S1. Dissolve oleic acid and oleylamine in n-heptane at a mass ratio of 1:1 to obtain a surfactant;

[0057] S2. The spinel high entropy oxide sample (CrMnFeCoCe)3O4 prepared by the solution combustion method is called sample A, and 1 g of the prepared sample A is placed in a quartz ball mill according to a ball-to-material ratio of 10:1, and 0.15 g of the prepared surfactant and 10 g of quartz grinding balls are added thereto, and the mixture is evenly ground at a speed of 1500 r / min for 18 h. After the grinding is completed, a large amount of ethanol is added to the ball mill to rinse, and the washed black suspension is transferred to a beaker, and allowed to stand for 30 min until the solution is separated, and the supernatant is poured out. The process is repeated 5 to 7 times until the poured supernatant is clear, does not appear light yellow, and the pH value is not acidic, so that the ball-milled catalyst is obtained;

[0058] S3, put 1g of ball-milled catalyst into a beaker, add 50ml of deionized water solution and stir thoroughly, then add hydrogen ions (H + ) was added with a 0.06M nitric acid solution, stirred at room temperature for 1 hour and then filtered, the resulting precipitate was filtered, washed with deionized water, and dried at 80°C for 12 hours to obtain the modified high entropy oxide catalyst.

[0059] The surface tension test of sample A before and after modification and the catalytic efficiency of o-xylene in a water-containing environment are shown in Figure 2. Figure 1 and Figure 2 As shown, after surface modification, the hydrophobicity of sample A is significantly increased. It is generally believed that samples with a surface hydrophobic angle of more than 120° can be called super-hydrophobic samples, and this sample reached 140° after modification, which means that the surface modification is basically successful, and the surface of sample A is successfully modified into a super-hydrophobic surface; therefore, a water resistance experiment was carried out within the experimental temperature range, and the experimental results showed that: within the experimental temperature range, 30 vol.% of water vapor could not interfere with the catalyst sample, and the catalytic efficiency of the catalyst remained basically constant.

[0060] In the embodiment of the present invention, the solution combustion method is an existing relatively mature material preparation technology. The specific preparation process of the spinel high entropy oxide sample (CrMnFeCoCe)3O4 is as follows: First, 10mmol of metal nitrates (Co(NO3)2·6H2O, Cr(NO3)2·9H2O, Mn(NO3)2 solution, Ce(NO3)2·6H2O and (Fe(NO3)2·9H2O)) are dissolved in 100mL of deionized water (DI), and then added 10g glycine (C2H5NO2), magnetically stir the mixture at room temperature for 30min to obtain a uniform red-brown solution. Then place the solution in a constant temperature oven at 70℃ and heat for 12h to remove excess deionized water, and finally obtain a red-brown colloid. The obtained red-brown gel is placed in a quartz boat and then placed in a tube furnace. After calcination in air atmosphere for 30min, the sample is directly quenched to room temperature and ground into powder to obtain a spinel high entropy oxide sample (CrMnFeCoCe)3O4.

[0061] In the embodiments of the present invention, the spinel high entropy oxide sample (CrMnFeCoCe)3O4 can also be prepared by other methods in the prior art, which has no effect on the embodiments of the present invention. The high entropy sample catalyst used for modification can be prepared by classical means including solution combustion, high-energy ball milling, etc., which has no obvious effect on subsequent modification.

[0062] Example 2

[0063] A method for modifying a high entropy oxide catalyst, in this embodiment, a 0.06M concentration nitric acid solution is used to acid-etch and ball-mill the high entropy oxide catalyst (MnLaCePrSm)O2, comprising the following steps:

[0064] S1. Dissolve oleic acid and oleylamine in n-heptane at a mass ratio of 1:1 to obtain a surfactant;

[0065] S2. The fluorite-type high entropy oxide sample (MnLaCePrSm)O2 is called sample B, and 1 g of the prepared sample B is placed in a quartz ball mill according to a ball-to-material ratio of 10:1, and 0.15 g of the prepared surfactant and 10 g of quartz grinding balls are added thereto, and the mixture is evenly ground at a speed of 1500 r / min for 18 h. After the grinding is completed, a large amount of ethanol is added to the ball mill to rinse, and the washed black suspension is transferred to a beaker, and allowed to stand for 30 min until the solution is separated, and the supernatant is poured out. The process is repeated 5 to 7 times until the poured supernatant is clear, does not appear light yellow, and the pH value is not acidic, and the ball-milled catalyst is obtained;

[0066] S3, put 1g of the ball-milled catalyst into a beaker, add 50ml of deionized water solution and stir thoroughly, then add hydrogen ions (H+ ) was added with a 0.06M nitric acid solution, stirred at room temperature for 1 hour and then filtered, the precipitate obtained by filtration was washed with deionized water, and dried at 80°C for 12 hours to obtain the modified high entropy oxide catalyst.

[0067] The catalytic efficiency of sample B before and after modification and the catalytic efficiency in aqueous environment are shown in Figure 3 and Figure 4 As shown in the figure, after surface modification, the hydrophobicity of sample B is significantly increased. It is generally believed that samples with a surface hydrophobic angle of more than 120° can be called super-hydrophobic samples, and this sample reached 140° after modification, which means that the surface modification is basically successful, and the surface of sample B is successfully modified into a super-hydrophobic surface; therefore, a water resistance experiment was carried out within the experimental temperature range, and the experimental results showed that: within the experimental temperature range, 30 vol.% of water vapor could not interfere with the catalyst sample, and the catalytic efficiency of the catalyst remained basically constant.

[0068] At the same time, the results of this section also prove that this modification method can be effective in high-entropy oxide catalysts of the fourth period, sixth period and different crystal types. The high-entropy oxides formed by doping between transition group elements of the fourth and sixth periods all have this property.

[0069] (CrMnFeCoCe)3O4, (CrMnFeCoCe)3O4, (MnLaCePrSm)O2. From the above three compounds, it can be seen that the high entropy oxide contains at least one element of the fourth period or the sixth period and at least one lanthanide metal.

[0070] Embodiment 3-9

[0071] A method for modifying a high entropy oxide catalyst, the seven embodiments are to prepare and perform performance tests on a high entropy sample A treated with acid etching at a concentration of 0.01-0.1 M according to a gradient, the steps are as follows:

[0072] The spinel high entropy oxide sample (CrMnFeCoCe)3O4 prepared by solution combustion method is called sample A. 1g of sample precursor is placed in a beaker, and 50ml of deionized water is added and stirred thoroughly. Then hydrogen ions (H + ) 0.01-0.1M nitric acid solution, then the mixture was stirred at room temperature for 1 hour and then filtered, the precipitate was filtered, washed with deionized water, and dried at 80°C for 12 hours, thus completing the surface acid etching modification, that is, the modified high entropy oxide catalyst was obtained. The catalytic efficiency of sample A before and after modification and the catalytic efficiency in the aqueous environment are shown in Figure 5 shown.

[0073] The experimental results show that within the experimental temperature range, the catalytic efficiency of the catalyst is significantly affected by the acid concentration. Among them, 0.06M concentration of nitric acid solution can significantly improve the catalytic ability of the catalyst. However, due to the lack of ball milling treatment, the water resistance and catalytic ability of the sample are not fully improved.

[0074] Comparative Example 1

[0075] A method for modifying a high entropy oxide catalyst, using a sample A without any modification: (CrMnFeCoCe)3O4 to test water resistance, comprising the following steps:

[0076] The sample A (CrMnFeCoCe) 3 O 4 prepared by the solution combustion method was directly subjected to water vapor concentration water resistance test experiments at 150°C, 200°C and 250°C respectively.

[0077] The experimental results are as follows Figure 6 and Figure 7 As shown, it is generally believed that samples with a surface hydrophobic angle of less than 30° can be called hydrophilic samples, and the hydrophobic angle of this sample before modification is only 16°, which basically means that sample A has good contact with water molecules; therefore, we conducted a water resistance experiment within the experimental temperature range, and the experimental results showed that within the experimental temperature range, the catalyst efficiency was greatly affected by water vapor, and the catalytic efficiency showed a high attenuation under the influence of 5 vol.% water vapor. Compared with the experimental group samples of Examples 1-9, which can maintain stable catalytic behavior in 30% water vapor, the water resistance of the unmodified catalyst is significantly insufficient.

[0078] Comparative Example 2

[0079] A method for modifying a high entropy oxide catalyst, using a sample A: (CrMnFeCoCe)3O4 that has only been subjected to ball milling modification to test water resistance, comprises the following steps:

[0080] The sample A: (CrMnFeCoCe)3O4 prepared by the solution combustion method was only ball-milled. According to the ball-to-material ratio of 10:1, 1 g of the prepared (CrMnFeCoCe)3O4 sample A was placed in a quartz ball mill, and 0.15 g of the prepared surfactant and 10 g of quartz grinding balls were added thereto. The mixture was evenly ground at a speed of 1500 r / min for 18 h. After the grinding was completed, a large amount of ethanol was added to the ball mill to rinse it, and the washed black suspension was transferred to a beaker and allowed to stand for 30 min until the solution was separated, and the supernatant was poured out. The process was repeated 5 to 7 times until the poured supernatant was clear, not light yellow, and the pH value was not acidic, thus obtaining the sample after ball milling.

[0081] Subsequently, the samples were subjected to water vapor concentration water resistance test experiments at 150°C, 200°C, and 250°C respectively. The experimental results showed that within the experimental temperature range, the catalyst efficiency was greatly affected by water vapor, and the catalytic efficiency showed a high attenuation under the influence of 5 vol.% water vapor. Compared with the experimental group samples of Examples 1-9, which can maintain stable catalytic behavior in 30% water vapor, the water resistance of the catalyst modified by ball milling alone is significantly insufficient.

[0082] Comparative Example 3

[0083] A method for modifying a high entropy oxide catalyst, using a catalyst precursor A that is only acid-etched:

[0084] The water resistance test of (CrMnFeCoCe)3O4 includes the following steps:

[0085] Sample A: (CrMnFeCoCe)3O4 prepared by solution combustion method was only subjected to acid etching modification. 1 g of the prepared (CrMnFeCoCe)3O4 sample A was placed in a beaker, and 50 ml of deionized water was added and stirred thoroughly. Then hydrogen ions (H + ) 0.06M nitric acid solution, stirred at room temperature for 1 hour and then filtered, the resulting precipitate was filtered, washed with deionized water, and dried at 80°C for 12 hours to complete the surface acid etching modification.

[0086] Subsequently, the samples were subjected to water vapor concentration water resistance test at 150°C, 200°C, and 250°C. The test results are as follows: Fig.10 and 11 As shown, the experimental results show that within the experimental temperature range, the catalyst efficiency is greatly affected by water vapor, and the catalytic efficiency shows a high attenuation under the influence of 9 vol.% water vapor. Compared with the experimental group samples of Examples 1-9, which can maintain stable catalytic behavior in 30% water vapor, the water resistance of the catalyst that is only modified by acid etching is significantly insufficient, but higher than the catalyst that is only modified by ball milling and without any modification.

[0087] Determination of water resistance in catalytic processes

[0088] Composition of simulated flue gas:

[0089] The gases required for the experimental process are composed of the basic flue gas simulation part and the interfering flue gas simulation part. The basic simulated flue gas is composed of a mixture of nitrogen, oxygen and o-xylene. High-purity oxygen (purity 99.99%) and high-purity nitrogen (purity 99.99%) are both from Tianjin Sizhi Gas Co., Ltd., and o-xylene (purity 100ppm, nitrogen balance gas) is from Beijing Haipu Gas Co., Ltd.; the interfering flue gas simulating the interfering components in the complex flue gas is water vapor, which is directly introduced into the mixing tank through a constant temperature water bath with nitrogen as the carrier gas. The concentration of water vapor is controlled by the calculated water bath temperature and the carrier gas flow rate of nitrogen.

[0090] Reaction bench and catalytic test methods and parameters:

[0091] like Fig.12 The flue gas test system shown can meet the target requirements of the experimental test, in which nitrogen, oxygen, o-xylene and other gases are directly drawn out from the gas cylinder, the flow of the relevant gas is directly controlled by the volume flow meter b and the mass flow meter a (D08-1F, Beijing Sevenstar Electronics Co., Ltd., China), and the concentration is measured by the flue gas analyzer k (KM940MKII, KANE, England); the water vapor is directly introduced into the mixing bottle e by using the washing bottle d filled with water placed in the constant temperature water tank c (SC-16, Ningbo Xinzhi Biotechnology Co., Ltd., China) to simulate the water vapor in the flue gas. The content of water vapor is controlled by the constant temperature water bath temperature and the amount of nitrogen carrier gas, and the specific data is obtained by calculating the saturated vapor pressure of water vapor; all the above participating reaction gases are directly introduced into the mixing bottle e after being drawn out and evenly mixed, and then passed into the quartz reactor g for testing.

[0092] The final overall gas environment in the quartz reactor g should be maintained at 0.1MPa, the same as the external atmospheric pressure. The concentration of VOCs in the overall gas environment is stable at 50ppm, the oxygen concentration is stable at 5vol.%, nitrogen is used as a carrier gas, and the water vapor content in the gas path should be stable as the only stable value between 5 and 30vol.%. The reaction temperature range of the quartz reactor is controlled between 150 and 450°C, and the specific value is stably controlled by the temperature controller j (AI-518P, Xiamen Yudian Co., Ltd., China) and the constant temperature tube furnace f (YDL, Huzhou Yuanyao Electric Technology Co., Ltd., China). Catalyst h is placed in the middle layer of quartz reactor g. During the experiment, the total gas flow rate is controlled to 200ml / min, and the amount of catalyst h is 0.4g, which can be appropriately adjusted to maintain the reaction space velocity at 30000h -1Before testing at each experimental point, the system needs to run for 30 minutes in a gas-stable state. The concentration of o-xylene at the outlet is directly measured using a VOCs tester i (SKY2000-M2, Shenzhen Yuante Technology Co., Ltd., China) and a flue gas analyzer k (KM940 MKII, KANE, England).

[0093] The removal efficiency of VOCs pollutants is calculated by formula (1):

[0094]

[0095] Here, η refers to the removal efficiency of pollutants, C(in) represents the concentration of o-xylene at the reactor inlet, and C(out) represents the concentration of o-xylene at the reactor outlet.

[0096] Gas components at the beginning and end of the experimental reaction:

[0097] At the beginning of the reaction, the gas components only include nitrogen, oxygen, o-xylene gas, and water vapor; after the reaction, the gas components, in addition to nitrogen, oxygen, o-xylene gas, and water vapor, contain carbon dioxide and a small amount of intermediate products such as formic acid and n-hexane, as shown by GC-MS testing.

[0098] Catalytic experiment of high entropy catalyst in anhydrous simulated flue gas:

[0099] Catalytic Experiment of High Entropy Oxide (CrMnFeCoCe)3O4 in Simulated Flue Gas of O-Xylene

[0100] When the catalyst dosage is 0.4 g, the oxygen flow rate is 10 ml / min, the o-xylene flow rate is 60 ml / min, the nitrogen flow rate is 130 ml / min, and the overall space velocity of the reaction environment is 30000 h -1 When the pollutant concentration is 50 ppm and the oxygen concentration is 5 vol.%, the removal efficiency of o-xylene is tested at a temperature of 200°C to 450°C.

[0101] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.

Claims

1. A method for modifying a high entropy oxide catalyst, characterized in that: The steps include: S1. preparing a surfactant; S2, adding grinding balls and a high entropy oxide catalyst into a ball mill, and adding the surfactant obtained in step S1, and performing a ball milling reaction. After the ball milling reaction is completed, ethanol is added for washing until the supernatant is clear, not light yellow, and the pH is not acidic, thereby obtaining a ball milled catalyst; S3, adding the ball-milled catalyst to deionized water to form a suspension, and adding a final concentration of H + The acidic solution with a concentration of 0.01 to 0.1 M is stirred, the obtained precipitate is filtered, washed with deionized water, and dried to obtain a modified high entropy oxide catalyst.

2. The method for modifying a high entropy oxide catalyst according to claim 1, characterized in that: The surfactant is a surfactant formed by mixing oleic acid and oleylamine in a mass ratio of 1:

1.

3. The method for modifying a high entropy oxide catalyst according to claim 2, characterized in that: The solvent for dissolving the oleic acid and oleylamine is n-heptane or carbon tetrachloride.

4. The method for modifying a high entropy oxide catalyst according to claim 1, characterized in that: The mass of the surfactant is 10% to 50% of the mass of the high entropy oxide catalyst.

5. The method for modifying a high entropy oxide catalyst according to claim 4, characterized in that: The amount of the surfactant used is 15 wt%.

6. The method for modifying a high entropy oxide catalyst according to claim 1, characterized in that: The acidic solution is a nitric acid solution, a sulfuric acid solution or a hydrochloric acid solution, and the concentration of the acidic solution is 0.06M; the ball-to-material ratio of the ball mill is 5-20:1, the ball milling rate is 1200-1500r / min, and the ball milling time is 12-36h.

7. The method for modifying a high entropy oxide catalyst according to claim 3, characterized in that: The high entropy oxide catalyst is a spinel high entropy oxide, a fluorite high entropy oxide, (CrMnFeCoCe)3O4, (MnLaCePrSm)O2 or (CoMnCuAlFe)3O4.

8. A high entropy oxide catalyst, characterized in that: The method of claim 1 is used for modification.

9. Use of the high entropy oxide catalyst according to claim 8 in catalytic removal of VOCs in wet flue gas.

10. The use according to claim 9, characterized in that: Wet flue gas contains 30% water vapor.